THE DEVELOPMENT OF QR CODE BASED MOBILE ATTENDANCE INFORMATION SYSTEM USING SCRUM FRAMEWORK - Muhammad Aqil Maulana; Sri Rahayu Natasia; Dwi Arief Prambudi; Tegar Palyus Fiqar (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2022)
As one of State ‘s Higher Education Institutions, the Kalimantan Institute of Technology (ITK) must perform the education and teaching function as mandated by the tri dharma perguruan tinggi, then the function is regulated in academic regulations and implemented in business processes of attendance. Currently, the attendances data are recapitulated manually at week 15 by Academic Staff. The attendance process that has been running has several problems, namely prone to violations of the actual meeting realization and attendance count, recapitulation time that takes a long time, risk of data input errors and loss of presence sheet. Based on these problems, the attendance information system is developed (SIAP ITK). This research was conducted with the agile software development methodology with the scrum framework. The results of this research is an android application following the business processes of attendance in ITK. Based on the testing result which was carried out during this research, SIAP ITK is considered capable of optimizing the attendance process that has been running at ITK.